2019
DOI: 10.1371/journal.pone.0224328
|View full text |Cite
|
Sign up to set email alerts
|

Application of national pollutant inventories for monitoring trends on dioxin emissions from stationary industrial sources in Australia, Canada and European Union

Abstract: Industrial sources, including iron ore sintering, municipal waste incineration and non-ferrous metal processing have been prominent emitters of dioxins to the environment. With the expanding industrial sectors, many international conventions were established in order to reduce the emission of dioxins in the past two decades. The Stockholm convention, a global monitoring treaty, entered into force in 2004 with the aim to promote development of strategies to reduce or eliminate dioxin emissions. According to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…TCDD is a serious human carcinogen according to the IARC [ 209 ]. Although TCDD use has been strictly regulated, some dioxin emission still arises from electric power plants, iron and steel industries, as well as nonferrous metal manufacturers [ 266 ]. Many epidemiological studies have shown a significant correlation between elevated serum TCDD concentration with a high risk of breast cancer in women [ 267 , 268 ].…”
Section: Xenoestrogens In Inflammation and Breast Cancermentioning
confidence: 99%
“…TCDD is a serious human carcinogen according to the IARC [ 209 ]. Although TCDD use has been strictly regulated, some dioxin emission still arises from electric power plants, iron and steel industries, as well as nonferrous metal manufacturers [ 266 ]. Many epidemiological studies have shown a significant correlation between elevated serum TCDD concentration with a high risk of breast cancer in women [ 267 , 268 ].…”
Section: Xenoestrogens In Inflammation and Breast Cancermentioning
confidence: 99%
“…This is mainly due to changes in technological processes and new regulations like the Stockholm convention in 2001. Nowadays, the main sources of dioxin emission arise from the production of electricity, iron and steel industries and non-ferrous metal production [205].…”
Section: Industrial Risk Management and Control Of Dioxin Releasementioning
confidence: 99%
“…7,11−16 For instance, ISI is the primary stationary industrial source of PCDD/Fs in Canada and the second highest in Europe, after electricity generation. 17 In summary, the emissions from ISI are environmental issues of global significance. 18 On a regional-to-global scale, the magnitudes of emissions from ISI are primarily determined by ISI production outputs and emission abatement measures.…”
Section: Introductionmentioning
confidence: 99%